2016
DOI: 10.1177/1548051816656004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Politics, Emotional Stability, and LMX on Job Dedication

Abstract: Efforts to identify antecedents of job dedication (i.e., being loyal and cooperative) are likely to offer value to managers. The authors examined the combined effects of organizational politics and emotional stability on the relationship between leader-member exchange and job dedication. Results of analyses conducted on 156 private sector workers revealed that leader-member exchange quality yielded high levels of job dedication among all employees except the emotionally unstable working in highly political cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 70 publications
1
33
0
2
Order By: Relevance
“…Employee loyalty is generally considered as an explicitly positive attribute at an individual and organizational levels. On the contrary, in individuals who experience a challenging or dysfunctional context, their loyalty may be torn between organizational loyalty and their response to that dysfunction such as feeling of threat to their personal wellbeing [47].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Employee loyalty is generally considered as an explicitly positive attribute at an individual and organizational levels. On the contrary, in individuals who experience a challenging or dysfunctional context, their loyalty may be torn between organizational loyalty and their response to that dysfunction such as feeling of threat to their personal wellbeing [47].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…When employees can count on the support and respect of their leaders, they may become less sensitive to the hardships associated with self-serving decision-making (Chang et al, 2012;Johnson et al, 2017), which should mitigate their beliefs that the organization does not care about their career development. Ultimately, the tendency to halt or limit their performance-enhancing activities might thus be contained more easily.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Employees' perceptions that their organization's decision-making processes are guided by dysfunctional political games represents a significant concern, because this adverse work condition can harm the employees' mental well-being and the quality of their organizational functioning (Chang, Rosen, & Levy, 2009;Johnson, Rogers, Stewart, David, & Witt, 2017). Such a political climate notably undermines the exchange expectations that employees have in terms of how their organization should treat them (Chang, Rosen, Siemieniec, & Johnson, 2012), which might become manifest in various ways, such as when employees believe that favouritism supersedes merit, a limited number of organizational members always get their way, their employer endorses a work-behind-thescenes mentality, or people do not dare speak up for fear of retaliation (De Clercq & Belausteguigoitia, 2017;Kacmar & Ferris, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we believe that individuals who address high degrees of work ethic, are moderately more proficient at managing workplace stressors and can help form positive job attitudes. However, a number of studies have refuted the stance taken by prior studies and therefore indicated a positive nature of POP in respect to the behaviors and attitudes of employees [13,14].…”
Section: Introductionmentioning
confidence: 99%